Phase I trial of hydroxychloroquine to enhance palbociclib and letrozole efficacy in ER+/HER2− breast cancer - Akshara Singareeka Raghavendra; Nicole M. Kettner; Danielle Kwiatkowski; Senthil Damodaran; Yan Wang; David Ramirez; Dan S. Gombos; Kelly K. Hunt; Yu Shen; Khandan Keyomarsi; Debu Tripathy (npj Breast Cancer)
Abstract Endocrine therapy with CDK4/6 inhibitors is standard for estrogen receptor-positive, HER2−negative metastatic breast cancer (ER+/HER2− MBC), yet clinical resistance develops. Previously, we demonstrated that low doses of palbociclib activate autophagy, reversing initial G1 cell cycle arrest, while high concentrations induce off-target senescence. The autophagy inhibitor hydroxychloroquine (HCQ) induced on-target senescence at lower palbociclib doses. We conducted a phase I trial (NCT03774472 registered in ClinicalTrials.gov on 8/20/2018) of HCQ (400, 600, 800 mg/day) with palbociclib (75 mg/day continuous) and letrozole, using a 3 + 3 design. Primary objectives included safety, tolerability, and determining the recommended phase 2 dose (RP2D) of HCQ. Secondary objectives included tumor response and biomarker analysis. Fourteen ER+/HER2− MBC patients were evaluable [400 mg (n = 4), 600 mg (n = 4), 800 mg (n = 6)]. Grade 3 adverse events (AEs) included hematological (3 at 800 mg), skin rash (2 at 600 mg), and anorexia (1 at 400 mg), with no serious AEs. The best responses were partial (2), stable (11), and progression (1). Tumor reductions ranged from 11% to 30%, with one 55% increase. The two partial responders sustained tumor size reductions of 30% to 55% over an extended treatment period, lasting nearly 300 days. Biomarker analysis in responders demonstrated significant decreases in Ki67, Rb, and nuclear cyclin E levels and increases in autophagy markers p62 and LAMP1, suggesting a correlation between these biomarkers and treatment response. This phase I study demonstrated that HCQ is safe and well-tolerated and the RP2D was established at 800 mg/day with continuous low-dose palbociclib (75 mg/day) and letrozole (2.5 mg/day). These findings suggest that adding HCQ could potentially enhance the efficacy of low-dose palbociclib and standard letrozole therapy, pending verification in larger randomized studies.